How to fly with broken wings - Elson, Jane (London : Hodder Children$1 (Bs Books ,s, 2015)
How to Fly with Broken Wings tells the powerful story of Willow, a girl growing up in a family facing serious difficulties. As her home life becomes increasingly unstable, Willow struggles with fear, responsibility, and silence. Through the support of school and caring adults, she begins to find the courage to speak up and protect herself and her younger brother. The novel explores themes of resilience, bravery, trust, and hope, showing how even in the hardest situations, young people can find their strength.